Higher maternal serum concentrations of nicotinamide and related metabolites in late pregnancy are associated with a lower risk of offspring atopic eczema at age 12 months. Issue 10 (15th September 2016) - El‐Heis, S.; Crozier, S. R.; Robinson, S. M.; Harvey, N. C.; Cooper, C.; Inskip, H. M.; ,; Godfrey, K. M.
Summary: Background: Evidence that atopic eczema partly originates in utero is increasing, with some studies linking the risk of developing the condition with aspects of maternal diet during pregnancy. Nicotinamide, a naturally occurring nutrient that is maintained through the dietary intakes of vitamin B3 and tryptophan, has been used in the treatment of some skin conditions including atopic eczema. Objective: To examine the relation of maternal serum concentrations of nicotinamide and related tryptophan metabolites to the risk of atopic eczema in the offspring. Methods: Within the UK Southampton Women Survey, infantile atopic eczema at ages 6 and 12 months was ascertained (modified UK Working Party Criteria for the Definition of Atopic Dermatitis). Maternal serum levels of kynurenine, kynurenic acid, anthranilic acid, tryptophan, nicotinamide and N1‐methylnicotinamide were measured in late pregnancy by mass spectrometry ( n = 497) and related to the odds ratio of infantile atopic eczema. Results: Maternal nicotinamide and related metabolite concentrations were not associated with offspring atopic eczema at age 6 months. Higher concentrations of nicotinamide and anthranilic acid were, however, associated with a lower risk of eczema at age 12 months (odds ratios 0.69, 95% CI 0.53–0.91/SD change, P = 0.007 and 0.63, 0.48–0.83, P = 0.001, respectively). The associations were robust to adjustment for potentially confounding variables. Conclusion and clinical relevance: This is the first study linking maternal serum concentrations of nicotinamide and related metabolites to the risk of atopic eczema in the offspring. The findings point to potentially modifiable maternal influences on this complex and highly prevalent condition.